A longitudinal study of plasma acylcarnitines throughout pregnancy and associations with risk of gestational diabetes mellitus. Issue 8 (August 2021) - Lin, Yuan; Wu, Jing; Zhu, Yeyi; Hinkle, Stefanie N.; Rawal, Shristi; Liang, Liming; Weir, Natalie L.; Tsai, Michael Y.; Zhang, Cuilin
Summary: Background & aims: Prospective and longitudinal data on the association between acylcarnitines and gestational diabetes (GDM) are lacking. This study aims to prospectively investigate 28 acylcarnitines in relation to subsequent GDM risk. Methods: Within the NICHD Fetal Growth Studies-Singleton Cohort, plasma levels of acylcarnitines and cardiometabolic biomarkers were measured at gestational week (GW) 10–14, 15–26, 23–31, and 33–39 among 107 GDM cases and 214 controls. Results: At GW 10–14, per standard deviation (SD) increased level of C14:1-OH was associated with a 55% increased risk of GDM after adjusting for major risk factors for GDM [OR (95% CI): 1.55 (1.05–2.29)]. At GW 15–26, C4, C8:1 and C16:1-OH were associated with an increased risk of GDM [OR (95% CI) for per SD increase: 1.42 (1.01–2.00), 1.41 (1.02–1.96), and 1.77 (1.10–2.84), respectively]. Whereas increased C10 and C18 were related to lower risk of GDM [OR (95% CI) for per SD increase: 0.74 (0.55–1.00), and 0.69 (0.49–0.97), respectively]. Moreover, we observed correlations of individual acylcarnitine with multiple clinical markers implicated in glucose homeostasis and cardiometabolic function among non-GDM women. Conclusions: Our results demonstrate that several plasma acylcarnitine species are differentially associated with GDM risk by chain length. Future studies are warranted to investigate the distinct roles of individual acylcarnitine in glucose homeostasis in pregnancy.